2022
DOI: 10.1186/s12885-022-10262-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinical significance of HER-2 low expression in early-stage gastric cancer

Abstract: Introduction Gastric cancer is the most fifth common tumor worldwide. Human epidermal growth factor receptor 2 (HER2) overexpression is associated with poor prognosis and clinical characteristics in gastric cancer. Nevertheless, the biology of HER2-low expression has not reported in gastric cancer. Materials and methods A total of 157 patients with early-stage gastric cancer were retrospectively analyzed. The associations between HER-2 low expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…However, its influence on prognosis remains controversial. Yang et al [ 32 ] suggested that low expression of HER2 might lead to distinct biological characteristics but was not an independent prognostic factor for early-stage gastric cancer’s disease-free survival (DFS) or OS. Jiang et al [ 33 ] demonstrated that the co-expression of Sp1 and HER-2 was associated with poor prognosis in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, its influence on prognosis remains controversial. Yang et al [ 32 ] suggested that low expression of HER2 might lead to distinct biological characteristics but was not an independent prognostic factor for early-stage gastric cancer’s disease-free survival (DFS) or OS. Jiang et al [ 33 ] demonstrated that the co-expression of Sp1 and HER-2 was associated with poor prognosis in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab in combination with chemotherapy and trastuzumab deruxtecan in tumors with HER2 high expression demonstrated a significant overall survival improvement compared with the group administered only chemotherapy, as the development of companion diagnosis and molecular-targeting therapeutic agents has progressed in recent years [ 13 , 14 ]. Furthermore, trastuzumab deruxtecan has been recently revealed to show clinical activity even in GC with low HER2 expression, and the importance of more accurate HER2 expression evaluation is increasing [ 31 ]. In the present study, we demonstrated that the time to specimen processing, the intestinal type of cancers and pM are independent factors involving HER2-positivity.…”
Section: Discussionmentioning
confidence: 99%
“…While the evaluation of human epidermal growth factor receptor 2 (Her2) has been routinely performed in patients with gastroesophageal AC for years and is a feasible surrogate parameter for the response to Her2 blockage in advanced settings [ 8 ], the role of Her2 and especially Her2-low expression in localized settings is still evaluated [ 9 ]. Although patient selection for targeted treatment still poses an issue for clinical trials, the analysis of Her2 expression remains robust [ 10 ].…”
Section: Molecular Markersmentioning
confidence: 99%